PENGEMBANGAN BLENDED PROBLEM-BASED LEARNING (BPBL) SEBAGAI PENUNJANG AKTIVITAS PEMBELAJARAN MATEMATIKA DI PERGURUAN TINGGI - ., Zakaria; Dewantara, Andi Harpeni (DIDAKTIKA, 2021)
Several previous studies have investigated the effectiveness and positive impacts of blended problem-based learning (BPBL). However, no study has been found that specifically provided the development process of BPBL in mathematics education. This study, therefore, aims to produce BPBL using LMS Moodle in mathematics learning. This is a development research using ADDIE model, which includes five stages; analysis, design, development, implementation, and evaluation. This article, however, specifically focuses on the first three stages; analysis, design and development. The product criteria in this article is focused on the validity aspect, in which the validity data were obtained from the judgments’ expert (two material experts and two instructional media experts) using validation sheets. The results of the quantitative validation from all experts presented an average score of 4,18 or in the very good category. While the qualitative results indicated that the product was good and can be implemented further with minor revisions. To conclude, the product developed in this study had met the valid ciriteria and could be continued in practicality and effectiveness tests at the implementation stage. Keywords: Development; ADDIE; blended problem-based learning; mathematics learning